Advantages and clinical significance of enhanced CT combined with BRAF V600E gene detection in the diagnosis of papillary thyroid carcinoma. (December 2022) - Zhang, Jing; Zhang, Jiali; Han, Jing
Highlights: There was no significant difference in the levels of serum tumor markers CEA, CYFRA21–1, NSE and CA125 between the two groups. Levels of serum markers CEA, CYFRA21–1, NSE and CA125 in patients were higher than the normal range. Enhanced CT combined with BRAF V600E gene detection can improve the diagnostic accuracy of PTC, and its clinical indicators and safety are superior to FNAC. Enhanced CT combined with BRAF V600E gene detection is conducive to the diagnosis of PTC and predict the malignant development of the tumor. Abstract: Background: The diagnosis of papillary thyroid carcinoma (PTC) remains the focus of clinical research. Studies have shown that the BRAFV600E gene mutation is closely related to the development of PTC. In this study, we used the advantages and clinical significance of enhanced CT combined with BRAFV600E gene testing in the diagnosis of PTC. Methods: A total of 170 PTC patients who received treatment in our hospital between January 2020 and December 2020 were collected and divided into group A (enhanced CT combined with BRAFV600E gene detection) and group B (fine needle aspiration cytology, FNAC) according to different diagnostic methods. We recorded the general information of the patients and measured the levels of serum tumor markers including carcinoembryonic antigen (CEA), cytokeratin fragment 19 (CYFRA21–1), neuron-specific enolase (NSE) and carbohydrate antigen 125 (CA125). After pathological diagnosis, the specificity, sensitivity, accuracy, positive predictive value, and negative predictive value of the two diagnostic methods were contrasted. The accuracy of the two methods and the pathological test in identifying benign lesions, malignant tumors, was also compared. Results: All patients' serum tumor markers CEA, CYFRA21–1, NSE and CA125 levels were above normal. The detection rate of specificity, sensitivity, accuracy, positive predictive value and negative predictive value of enhanced CT combined with BRAF V600E gene detection were superior to those of FNAC. And the accuracy of enhanced CT combined with BRAF V600E gene detection, which was confirmed by corresponding pathological detection results, was significantly increased ( P < 0.05). Conclusions: Enhanced CT combined with BRAF V600E gene detection can improve the diagnostic accuracy of PTC, and its clinical indicators and safety are superior to FNAC.